PENGARUH PROMOSI KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN KUALITAS TIDUR PADA LANSIA HIPERTENSI DI POSYANDU BINTANG WILAYAH KERJA PUSKESMAS LEMPAKE SAMARINDA - rusdi, romadhona; Widyastuti, Dwi; Milkhatun, Milkhatun (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2024)
Background: Aging is often associated with hypertension, which increased from 4.5% in 1971 to 10.7% in 2020 in Indonesia. Sleep disturbances are common among the elderly and can negatively impact health. This study evaluates the effect of health promotion on knowledge of sleep quality in elderly individuals with hypertension at Posyandu Lansia Bintang, employing video-based education to enhance understanding of the relationship between sleep patterns and hypertension. Objective: To determine health promotion's impact on sleep quality knowledge in elderly individuals with hypertension. Method: This study utilized a quantitative approach with a pre-experimental design using a One Group Pretest-Posttest method. Measurements were conducted before and after the health promotion intervention focused on knowledge of sleep quality. Results: The study analyzed the characteristics of 38 elderly individuals with hypertension and the impact of health promotion on their knowledge of sleep quality. Most respondents were 60-74 years old (78.9%) and female (76.3%). Before the promotion, 100% had moderate knowledge; after the intervention, the percentage of those with good knowledge increased to 76.3% (p < 0.05). These findings highlight the importance of education on sleep quality for the health of elderly individuals with hypertension. Conclusion: The study at Posyandu Lansia Bintang, Puskesmas Lempake Samarinda, examined the influence of health promotion on the knowledge of elderly individuals with hypertension regarding sleep quality. Key findings indicate that most respondents were 60-74 years old (78.9%) and female (76.3%); 47.4% had no formal education. Poor sleep quality was prevalent, and there was a high prevalence of hypertension among the elderly. A significant relationship was found between sleep quality and blood pressure (p-value 0.001).